2020
DOI: 10.1093/rheumatology/keaa733
|View full text |Cite
|
Sign up to set email alerts
|

A clinical prediction model for estimating the risk of developing uveitis in patients with juvenile idiopathic arthritis

Abstract: Objective To build a prediction model for uveitis in children with JIA for use in current clinical practice. Methods Data from the international observational Pharmachild registry were used. Adjusted risk factors as well as predictors for JIA-associated uveitis (JIA-U) were determined using multivariable logistic regression models. The prediction model was selected based on the Akaike information criterion. Bootstrap resampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
1
19
1
1
Order By: Relevance
“…Subsequently, ΔCp of PAX1 and ZNF582 were considered for inclusion into a multivariable logistic regression model to predict the primary outcome. The model was developed by assessing the area under the receiver operating characteristic curve (AUC) in the training data and 10-fold cross-validation, validated, and adjusted by bootstrap resampling [ 28 , 29 ]. The final formula was as follows: ΔCp Model = 0.1*ΔCp PAX1 + 0.9*ΔCp ZNF582 + 2.032.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, ΔCp of PAX1 and ZNF582 were considered for inclusion into a multivariable logistic regression model to predict the primary outcome. The model was developed by assessing the area under the receiver operating characteristic curve (AUC) in the training data and 10-fold cross-validation, validated, and adjusted by bootstrap resampling [ 28 , 29 ]. The final formula was as follows: ΔCp Model = 0.1*ΔCp PAX1 + 0.9*ΔCp ZNF582 + 2.032.…”
Section: Methodsmentioning
confidence: 99%
“…Uveitis might be a risk factor of more severe course of JIA. In previous studies, it was shown that the JIA category, e.g., oligoarthritis, is an independent risk factor of uveitis when combined with ANA-positivity and early age of the JIA onset ( 13 15 ). It is well-established that persistent oligoarthritis and extended oligoarthritis have the highest probability of developing uveitis, while, in systemic and RF-positive categories, uveitis occurs extremely rarely ( 5 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the anti-CCP antibody was negative in JIA-U patients of this study, as previous studies. 2,4,9 Anti-CCP antibody positivity is more common in RF-positive polyarthritis, which has an aggressive and erosive disease course, but a lower uveitis occurrence rate. 25,26 Consistent with previous studies which reported RF-positive polyarthritis was protective against JIA-U, 4,21 uveitis did not occur in RF-positive polyarthritis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8−10 On the other hand, late onset of JIA, rheumatoid factor (RF)-positive polyarthritis, systemic arthritis, and positivity of anti-cyclic citrullinated peptide (CCP) antibodies are suggested as protective factors against JIA-U. 2,4,9 Nevertheless, there are still few studies on the clinical features and risk factors for JIA-U in Asian or Korean children. Identifying patients at higher risk of JIA-U is important for the appropriate screening, early diagnosis, and timely treatment of uveitis, as well as for understanding the pathophysiology of JIA and JIA-U.…”
Section: Introductionmentioning
confidence: 99%